Biphasic Porous Structures formed by Monomer/Water Interface Stabilization with Colloidal Nanoparticles (Adv. Mater. Interfaces 21/2021). Issue 21 (10th November 2021) - Pizzetti, Fabio; Rossetti, Arianna; Marchetti, Alessandro; Castiglione, Franca; Vanoli, Valeria; Coste, Elena; Veneruso, Valeria; Veglianese, Pietro; Sacchetti, Alessandro; Cingolani, Alberto; Rossi, Filippo
Abstract : Biphasic Porous Structures In article number 2100991, Fabio Pizzetti, Filippo Rossi, and co‐workers report biphasic porous structures consisting of monomer (hydrophobic, that can polymerize in bulk condition) and water can be formed simply by mixing the system using colloid nanoparticles without the typical presence of surfactants. The produced system exhibits high stability at body temperature and promising performances for multi‐drug delivery approach.